The Influence of Principal Performance on Teachers’ Pedagogical Competence - Heru Siswanto; Hasan Hariri; Sowiyah Sowiyah; Ridwan Ridwan (Journal of Social, Humanity, and Education, 2020)
Purpose: The principal's job is very essential and governs the equal of student learning consequences. Principal performances are also in line with teachers' output and self-esteem. In this case, it can be said that the principal's working area creates a feeling of comfort for teachers. The principal performances create the feeling at home in encouraging teachers and employees to work in harmony with the rules and programs that have been delineated so that work output becomes great and pupil learning outcomes also upsurge. One of the teachers’ productivity can be seen from the teachers’ pedagogical proficiency. Pedagogical proficiency is a talent for understanding students and management of educational and dialogical learning. This study targets to determine in what way the impact of the principal’s performance on teachers’ pedagogical competence. Methodology: The method used is the method of search and review. The review process starts with the search engine, Google scholar and reviewing related articles about principal performance and teachers’ pedagogical competence. Results: The results from 22 reviewed articles are that the role of the principal’s performance is very influential in affecting the teacher's pedagogical competence. Conclusions: Effective school principals enhance teachers’ pedagogical competence and student outcomes through leadership, support, and feedback, highlighting the need for principal training to improve overall educational quality. Limitations: Since this study includes many cases, further research could include performing to analyze how principal performance could affect teacher pedagogical competence. Contributions: This study can be useful in Faculty of Teacher Training and Education Lampung University and secondary education level.